Optimizing power consumption in novel electrical design for single ended comparator circuit - Zghoul, Fadi Nessir; Migdadi, Wafaa; Al-Mistarihi, Mamoun (Institute of Advanced Engineering and Science, 2025)
Contemporary society electronic technology has evolved into a pivotal component across various facets of our lives. Its indispensability is particularly evident in the advancement of medical, agricultural, industrial, and other sectors. As this technology continues to play a crucial role, optimizing its performance in terms of speed, accuracy, and energy consumption becomes paramount. This paper introduces a novel electrical design for the threshold inverter quantization comparator circuit aiming to meet the evolving demands of modern electronic applications. The proposed design enhances the classic threshold inverter quantization comparator’s performance by significantly reducing its power consumption. Through rigorous mathematical analysis and simulation results it is demonstrated that the proposed comparator design achieves a remarkable 50% reduction in power consumption compared to the conventional threshold inverter quantization comparator. Subsequently the newly devised design is applied to the construction of a 4-bit flash analog-to-digital converter using 0.35 μm complementary metal–oxide–semiconductor (CMOS) technology.